Accelerated glacier mass loss with atmospheric changes on Mt. Yulong, Southeastern Tibetan Plateau - Yan, Xingguo; Ma, Jinzhu; Ma, Xiaoyi; Wang, Shijin; Chen, Peiyuan; He, Yuanqing (Journal of hydrology (Amsterdam), 2021)
•12-years of continuous in-situ measurements of mass balance.•The glacial accumulation fell far short of offsetting the ablation.•The significant glacier retreat and deficit are attributed to regional warming. Glacier mass balance provides a sensitive barometer of climate-glacier interactions, yet only a few glaciers have been continuously well-documented. Here we evaluated the retreat status of Baishui River Glacier No. 1 (reference glacier of Yulong Snow Mountain) during the 1951–2020 period and explored its response to climate change. In particular, based on 12-years of continuous in-situ measurements, we presented the first comprehensive set of mass balance for the Baishui River Glacier No. 1 from 2008 to 2020. The result shows that the Baishui River Glacier No. 1 suffered sustained shrinkage in terms of both its area (which fell by 36 %) and reserves (with cumulative mass losses over 32.38 ± 3.62 m w.e.) over the past 70-years. The terminus rose from 4100 m asl in 1982 to 4395 m asl in 2017. The equilibrium line altitude has risen above the glacier’s summit since 2010, and the accumulation zone disappeared. Since the 1980s, the acceleration of glacier retreat has become established, and has been further strengthened after 2000, this corresponds to the process of climate warming. In-situ measurements showed that any glacial accumulation during the non-monsoon period (with a multiyear mean of 0.53 ± 0.08 m w.e.) fell far short of offsetting the ablation driven by both air temperature and liquid precipitation in the monsoon season (with a multiyear mean of 2.08 ± 0.20 m w.e.), meaning that the glacier could not attain a state of equilibrium, and quickly lost a significant mass (with multiyear mean losses of 1.54 ± 0.30 m w.e.). Given that, the current atmospheric conditions are unlikely to allow Baishui River Glacier No. 1 to suppress its loss trend.